Evaluation of mixed mode (I/II) notch stress intensity factors of sharp V-notches using point substitution displacement technique - Mirzaul Karim Hussain; K.S.R.K. Murthy (Fracture and Structural Integrity)
In this paper, determination of the accurate notch stress intensity factors (NSIFs) have been demonstrated using a recently proposed technique: The point substitution displacement technique (PSDT) for the sharp Vnotched configurations. In this technique, certain optimal point(s) on the notch flanks are obtained where the displacements are found to be highly accurate. Using the PSDT, the NSIFs are determined from the finite element (FE) displacements at these optimal point(s). The NSIFs of one pure mode I and two mixed mode (I/II) examples have been determined and excellent agreement of the present results with the published results is observed. The PSDT is efficient, robust and easy to be implemented in the available FE code.